Analisis Makna Dan Tanda Pada Desain Logo Galeri Sulaman Pinjaik Patah - Eti Fitri Nurhandayani; Dian Fitriani (UNIVERSITAS INDO GLOBAL MANDIRI, 2025)
This study reviews the in-depth deconstruction of the Pinjaik Patah Embroidery Gallery logo to identify and interpret the semiotic meaning contained therein. As a visual icon, this logo is considered a representation of the values ​​and cultural identity inherent in the handicraft business from Nagari Panampuang, West Sumatra. This study adopts a qualitative paradigm and uses Peirce's semiotic analysis. Through this approach, the study aims to analyze and interpret the meaning and signs contained in the logo design. Data collection techniques were carried out through observation and literature study. The results of this study found that the analyzed logo consists of two main elements, namely a logogram in the form of a broken needle stylization that functions as the main icon by directing to the source of life and unifying and a logotype that adopts organic motifs typical of Minangkabau so as to give a soft and natural impression. Through a semiotic approach, this study seeks to provide theoretical contributions to visual communication design practitioners in systematically identifying the various semiotic elements used in certain design works.